"Who is gullible to political disinformation?" : predicting susceptibility of university students to fake news. Issue 2 (3rd April 2022) - Bringula, Rex P.; Catacutan-Bangit, Annaliza E.; Garcia, Manuel B.; Gonzales, John Paul S.; Valderama, Arlene Mae C.
ABSTRACT: This study determined the items that could predict university students' susceptibility to disinformation (e.g., fake news). Toward this goal, randomly-selected students from the four private universities in Manila answered a content-validated and pilot-tested survey form. Through binary logistic regression analysis, it was found that frequent visits to Instagram, sharing a political post of a friend, and liking a post of a political party could increase the susceptibility of students to fake news. On the other hand, sharing the post of a political party, and seeking the opinion of experts could decrease the susceptibility of students to fake news. Of these items, liking a post with a similar opinion of a political party – a confirmation bias – had the highest contribution to fake news susceptibility of students. It is worth noting that the most reliable source of information, i.e. the library, is the least utilized fact-checking resource. It can be concluded that technological, internal, and external factors contribute either positively or negatively to the susceptibility of students to fake news. Implications to combat fake news are offered.